Isolation and identification of exopolysaccharides-producing lactic acid bacteria from conventional Egyptian dairy products - Elkashef, Hany; Moussa, Abdelfattah; Shawky, Islam; Elshaghabee, Fouad (Indian Journal of Dairy Science, 2025)
Previously, lactic acid bacteria (LAB) with noteworthy functional attributes have been assessed as conceivable probiotic candidates. Isolation and identification of novel exopolysaccharides-producing LAB from conventional Egyptian dairy products (Laban Rayeb, Kareish cheese, Labneh, baramily cheese, traditional yogurt, and cheese whey) and the probiotic properties of strains were studied. Isolated five LAB strains were identified as Lacticaseibacillus paracasei (S1 and S3), Enterococcus hirae S2 and Enterococcus durans S4. Enterococcus hirae S2 and Lacticaseibacillus paracasei S3 showed the highest exopolysaccharides yield ability. Enterococcus hirae S2 and S5 and Lacticaseibacillus paracasei S3 strains appeared high tolerance to low pH, bile salt, and artificial gastric juice. Some identified strains exhibited resistance and the others were sensitive to a wide range of antibiotics except Enterococcus hirae S5 that showed sensitive to all tested antibiotics. A cold storage had a positive effect on the viable count of Enterococcus durans S4. Our findings revealed that Lacticaseibacillus paracasei S3 and Enterococcus hirae S2 strains might be suitable probiotic candidates for producing functional food products.